2013
DOI: 10.1080/17437199.2013.820986
|View full text |Cite
|
Sign up to set email alerts
|

Can the common-sense model predict adherence in chronically ill patients? A meta-analysis

Abstract: The aim of this meta-analysis was to explore whether mental representations, derived from the common-sense model of illness representations (CSM), were able to predict adherence in chronically ill patients. Electronic databases were searched for studies that used the CSM and measured adherence behaviour in chronically ill patients. Correlations from the included articles were meta-analysed using a random-size effect model. A moderation analysis was conducted for the type of adherence behaviour. The effect size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 51 publications
4
51
1
3
Order By: Relevance
“…Cognitive representation was formed in parallel with the emotional representation. Emotional representations of feeling can be triggered by illness, for example, the diagnosis of chronic diseases can lead to anxiety or depression [6] . DM disease can have an impact on quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive representation was formed in parallel with the emotional representation. Emotional representations of feeling can be triggered by illness, for example, the diagnosis of chronic diseases can lead to anxiety or depression [6] . DM disease can have an impact on quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…
Despite Leventhal et al (2016) providing a 50-year overview of their Common-Sense Model of Self-Regulation (CSM), they fail to cite the null findings in relation to the CSM and adherence, as found by at least two reviews (Brandes & Mullan, 2014;Law et al, 2014).Brandes and Mullan (2014) Moderate to high heterogeneity was also evident for all dimensions apart from timeline, coherence and emotional representations, with funnel plots indicative of bias. These results are not supportive of the CSM for predicting adherence, in contrast to the conclusions of Leventhal et al, which cites other meta-analyses, but not this evidence or indeed that of Law et al
…”
mentioning
confidence: 99%
“…Despite Leventhal et al (2016) providing a 50-year overview of their Common-Sense Model of Self-Regulation (CSM), they fail to cite the null findings in relation to the CSM and adherence, as found by at least two reviews (Brandes & Mullan, 2014;Law et al, 2014).…”
mentioning
confidence: 99%
“…A meta-analysis found that illness perceptions alone are not a strong predictor of medication adherence within or across different conditions. 188 This is not completely surprising as the Common Sense Model suggests that for an individual to undertake a positive health behaviour it must make 'common sense' to them given their illness perceptions. 157 Compared to beliefs about medicines, illness perceptions may be more useful for understanding an individual's adherence behaviour, rather than making population level prediction across different chronic conditions.…”
Section: Relationship Between Illness Perceptions and Medication Adhementioning
confidence: 99%
“…Generally, a single model of health behaviour does not predict a large portion of variance in medication adherence. 124,188 Most studies investigate how beliefs derived from one health behaviour model correlate to a measure of medication adherence. This has limited our ability to understand how different beliefs come together to influence medication-taking behaviour.…”
Section: Relying On a Single Health Behaviour Modelmentioning
confidence: 99%